Upscale production of instant coconut milk-based rice porridge with mungbean snack food ginataang monggo - Mafe, Laurice Adona; Azanza, Ma. Patricia V. (2000)
ABSTRACT This study was developed to produce upscale production of instant guinataang mungo. Production procedures were based on a laboratory production scale of instant guinataang mungo product developed by Basman (1997). This study utilized Quick Cooking Rice QCR at 500 and 1000g levels of production. Dried mung beans were produced in 100 and 500g levels. Compounding of the instant mix was modified by decreasing the amount of coconut milk, sugar and ʎ-carrageenan from original Basman (1997) formulation. Iodized salt was also added to improve the flavor of the final mix. The rehydrated modified formulation was described as cream in color, with a neither thick nor thin consistency, slightly sweet, with soft rice and mung bean components. The overall acceptability was like slightly. Re-modification was done to improve the consistency of the rehydrated product by decreasing the amount of water by 30%. The rehydrated re-modified formulation, was described to be slightly cream in color, moderately thick in consistency, slightly sweet porridge with soft rice and mung bean. The overall acceptability of the product increased to like moderately. This re-modified formulation has a pH of 6.30 for both the dry processed and rehydrated instant mix. the water activity, (Aw) for the dry re-modified processed instant guinataang mungo was found to be <0.40. The Total Plate Count (TPC) of the instant and rehydrated product were 10 raised to 5 cfu/g and 10 raise to 4 cfu/g, respectively. The yeast and mold counts (YMC) for both the processed and rehydrated instant product showed a <10cfu/g. it was recommended to study the shelf life of this food commodity. It was also suggested to test the performance of the commodity as a disaster food prepared in community disaster center and sensory acceptance assessed by evacuation panelists. Appropriate types of packaging materials should also be studied to extend the shelf life of the product.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Snack foods